Promoting Higher Education Abroad Program in Science and Engineering to Indonesian High Schools: Methods, Challenges and Recommendations - F. Triawan; M. K. Biddinika; S. Hanaoka; B. A. Budiman (Faculty of Engineering and Technology, Sampoerna University, 2019)
This paper examines the promotional activities of higher education abroad program of Tokyo Institute of Technology (Tokyo Tech), Japan, namely Global Scientists and Engineers Program (GSEP), that was carried out in Indonesia. The objective is to document the lessons learned in the form of promotional methods, to identify the challenges, and to summarize some reccomendations. GSEP is an international Bachelor of Engineering degree program in Tokyo Tech majoring in Transdisciplicnary Scince and Engineering that is launched in 2015. This program is fully taught in English, thus it expects to attract more international students, such as from Asian countries, to pursue higher education in Tokyo Tech. For this reason, the promotional activities in Indonesia was done in August 2016 by presentation in front of thirteen high schools in Jakarta and nearby. For improvement of future promotion effort, participants were requested to express their evaluation regarding content and delivery of the material presentation by fulfilling questionnaire survey. The results reveal several interesting facts about Indonesian high school students, such as their willingness to study abroad even without scholarship, and some important aspects on how to effectively promote higher education abroad program in science and engineering in Indonesia.